Evaluation of Panti Rapihku Hospital Online Registration Application Based on Android: Evaluasi Aplikasi Pendaftaran Online Rumah Sakit Panti Rapihku Berbasis Android - Kurniawan, Henokh Sony; Sutrisno, Trismianto Asmo; Wariyanti, Astri Sri (Procedia of Engineering and Life Science, 2025)
Electronic Government (e-government) utilizes information technology to enhance government performance and public services. Electronic Medical Records (EMR) are mandatory to be implemented in all healthcare facilities in Indonesia to improve services and maintain data confidentiality. Usability is a crucial aspect in the success of applications and websites, including in the healthcare context. Observations of the PantiRapihku application revealed several issues: difficulties in use by patients, absence of a direct payment menu, account limitations, and mismatched doctor schedules. This study aims to evaluate the online registration application of Panti Rapih Hospital using the System Usability Scale (SUS).This descriptive study involved users who tried the PantiRapihku application. The sampling technique used was simple random sampling with a total sample of 30 respondents. Data were collected using the System Usability Scale (SUS) and analyzed descriptively using computer software.The SUS evaluation results showed a score of 83.4, indicating that the PantiRapihku application is in the “Acceptabel” category. The application’s grade scale level is in category B, and the adjective rating is in the “Excellent” category. The PantiRapihku application is well-rated and acceptabel to users. However, it is recommended that the hospital improves the application’s consistency and coherence, such as synchronizing patient registration history with doctor leave schedules and surgery schedules.